2006
DOI: 10.1016/j.chembiol.2006.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Facially Amphiphilic Antibacterial Oligomers with Conformationally Stiff Backbones

Abstract: A foldamer has been designed with a conformationally stiff backbone that is facially amphiphilic. The oligomer has excellent antimicrobial activity and was found to be 18 times more active toward bacterial cells than human red blood cells. The oligomer is built from arylamide bonds around a central 4,6-dicarboxy pyrimidine ring. The conformation was studied by X-ray crystallography and solution NMR spectroscopy. Density-functional (DFT) calculations were performed to guide the design. These calculations accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
98
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(102 citation statements)
references
References 70 publications
2
98
0
2
Order By: Relevance
“…The effect of guanidine for amine replacements of 4,6-disubstituted arylamide foldamers Table 3. The effect of guanidinylation of 5-monosubstituted arylamide foldamers substituents in 4c (24), prompting the synthesis of pyrimidinecontaining compound 6d. In vitro, compounds 6c and 6d were highly activity against a variety of Gram-positive and Gramnegative bacteria (Table 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of guanidine for amine replacements of 4,6-disubstituted arylamide foldamers Table 3. The effect of guanidinylation of 5-monosubstituted arylamide foldamers substituents in 4c (24), prompting the synthesis of pyrimidinecontaining compound 6d. In vitro, compounds 6c and 6d were highly activity against a variety of Gram-positive and Gramnegative bacteria (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies reported antibiotics designed to follow the mechanism of natural AMPs, for example, peptides composed of ␣-amino acids (15)(16)(17), ␤-amino acids (18,19), peptoids (20), aromatic oligomers (21)(22)(23)(24), and synthetic polymers (25)(26)(27). Previously, we designed a series of arylamide foldamers that showed potential for both activity and selectivity (21).…”
mentioning
confidence: 99%
“…5A and B). 12 It is obvious that the structure without the central pyrimidine ring (Fig. 5B) was not confined to the linear conformation.…”
Section: Novel Smamps: the Evolution Of The Aryl Oligomer Designmentioning
confidence: 94%
“…12 The pyrimidine arylamide with three rings (Fig. 5C) had an MIC of 0.8 lg mL −1 compared to its non-pyrimidine analogue which had an MIC of 12 lg mL −1 .…”
Section: Novel Smamps: the Evolution Of The Aryl Oligomer Designmentioning
confidence: 94%
See 1 more Smart Citation